Management of lateral skull base cancer: United Kingdom National Multidisciplinary Guidelines. (May 2016) - Homer, JJ; Lesser, T; Moffat, D; Slevin, N; Price, R; Blackburn, T
Abstract: This is the official guideline endorsed by the specialty associations involved in the care of head and neck cancer patients in the UK. It provides recommendations on the work up and management of lateral skull base cancer based on the existing evidence base for this rare condition. Recommendations: All patients with more than one of: chronic otalgia, bloody otorrhoea, bleeding, mass, facial swelling or palsy should be biopsied. (R) Magnetic resonance and computed tomography imaging should be performed. (R) Patients should undergo audiological assessment. (R) Carotid angiography is recommended in select patients. (G) The modified Pittsburg T-staging system is recommended. (G) The minimum operation for cancer involving the temporal bone is a lateral temporal bone resection. (R) Facial nerve rehabilitation should be initiated at primary surgery. (G) Anterolateral thigh free flap is the workhorse flap for lateral skull base defect reconstruction. (G) For patients undergoing surgery for squamous cell carcinoma, at least a superficial parotidectomy and selective neck dissection should be carried out. (R)